2011
DOI: 10.1021/ic2014013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Luminescent Iridium(III) Complexes Bearing Aryltriazole Cyclometallated Ligands

Abstract: Herein we report the synthesis of 4-aryl-1-benzyl-1H-1,2,3-triazoles (atl), made via "Click chemistry" and their incorporation as cyclometallating ligands into new heteroleptic iridium(III) complexes containing diimine (N(^)N) ancillary ligands 2,2'-bipyridine (bpy) and 4,4'-di-tert-butyl-2,2'-bipyridine (dtBubpy). Depending on decoration, these complexes emit from the yellow to sky blue in acetonitrile (ACN) solution at room temperature (RT). Their emission energies are slightly blue-shifted and their photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
221
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(255 citation statements)
references
References 75 publications
26
221
0
Order By: Relevance
“…360 nm) compared to 1 due to presence of the electron-withdrawing fluorine atoms on the C^N ligands, which stabilize the highest occupied molecular orbital (HOMO) and consequently increase the band gap. 25 The energy levels of the frontier orbitals of 1 and 2 are given in Figure S78. and ZnTPP-pyridine after mathematical subtraction of the absorption of free ZnTPP.…”
Section: S80 Respectively) a Comparison With The Td-cam-b3lyp Resulmentioning
confidence: 99%
“…360 nm) compared to 1 due to presence of the electron-withdrawing fluorine atoms on the C^N ligands, which stabilize the highest occupied molecular orbital (HOMO) and consequently increase the band gap. 25 The energy levels of the frontier orbitals of 1 and 2 are given in Figure S78. and ZnTPP-pyridine after mathematical subtraction of the absorption of free ZnTPP.…”
Section: S80 Respectively) a Comparison With The Td-cam-b3lyp Resulmentioning
confidence: 99%
“…We, and others, have paid particular attention to the use of copper-catalysed coupling of alkynes and azides to form 1,2,3-triazole-based ligands [7][8][9][10] and have investigated the photophysical properties of their resultant complexes. A significant number of reports have appeared detailing the photophysical and photochemical properties of triazole-based complexes of Re(I), Ru(II) and Ir(III) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Examples of triazole-containing complexes of osmium(II)…”
Section: Introductionmentioning
confidence: 99%
“…Although initial attempts demonstrated that A could promote the desired reaction, it was found that optimum yields were obtained when using the more reducing photocatalyst Ir[dF(Me)ppy] 2 (dtbbpy)PF 6 ( E ) 17. We were delighted to discover that simple cycloalkane carboxylic acids of various ring sizes and acyclic secondary carboxylic acids reacted to give the corresponding alkyl boronic esters in moderate to good yields ( 31 – 35 ).…”
mentioning
confidence: 99%